The Role Of Higher Education In Human Resource Development Shariah Economy In Indonesia - Madnasir, Madnasir; Satriawan, Dedi (LPPM Universitas PGRI Sumatera Barat, 2024)
This research analyzes the role of universities in developing professional Sharia Economic SDI (Insani Resources) to compete in the world of work, which ultimately has an impact on the development of Islamic Economics in Indonesia. The title of this research is the Role of Higher Education in Sharia Economic Human Resource Development (Study in the Superior Accredited Sharia Economic Study Program by LAMEMBA). The aim is to analyze, identify and also develop strategic steps for the role of the Sharia Economic Study Program in developing Sharia Economic Human Resources in Indonesia. This research uses qualitative research. The qualitative research design in this study uses a field and literature study approach, because this method is considered to be able to explain and answer the problems that this research wants to know. The data sources that researchers obtained to solve problems in this research were from literature (library research) as secondary data and field data (field research) as primary data. Data analysis, namely organizing data, making memos, describing and concluding. The following are some of the main roles and contributions of the two institutions: a) Education and Training of Professional Staff; b) Development of Sharia-Based Curriculum and Modules; c) Research and Development of Sharia Economics; d) Collaboration with Industry and Stakeholders; e) Public Socialization and Education about Sharia Economics; and f) Sharia Entrepreneurship Development.